Do Wage Expectations Influence the Decision to Enroll in Nursing College? - Jürg Schweri; Joop Hartog (Institute for the Study of Labor (IZA), 2015)
As Switzerland experiences a severe shortage of nurses, this paper investigates the impact of students' ex ante wage expectations on their choice to pursue a nursing college education. This analysis contributes to a small yet rapidly developing body of literature that uses subjective expectation data to predict educational choices. We surveyed a full cohort of healthcare trainees in their third year of training. The main result is that those trainees (in upper-secondary education) who expected a greater return from nursing college (tertiary education) were more likely to enroll in nursing college later on. This suggests that policies that increase returns from studying nursing can attract students to nursing. In addition, the results confirm that subjective wage expectation data are useful in modeling individual choice.
Keywords: I11; I21; J24; J31; D84; 330; college choice; fractional regression; healthcare; human capital; nursing; subjective expectations; training; wage